2022
DOI: 10.1007/s10340-022-01478-4
|View full text |Cite
|
Sign up to set email alerts
|

Silicon fertilisation affects morphological and immune defences of an insect pest and enhances plant compensatory growth

Abstract: Herbivorous insects have evolved various anti-predator defences, including morphological, behavioural, and immune defences, which can make biocontrol of herbivorous pests challenging. Silicon (Si) accumulation in plants is a potent physical defence against mandibulate insects. However, it remains uncertain how Si affects the anti-predator defences of insect herbivores and plant defences following herbivory. We grew the model grass, Brachypodium distachyon, hydroponically with (+Si) or without (–Si) Si and inve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…These results are in agreement with [66], who also found similar results when studying a soil dwelling herbivore interacting with sugarcane and Si. However, [25] observed increased values of phenol oxidase activity in the hemolymph of H. armigera larvae fed on the Si-fertilized model grass Brachypodium distachyon. Despite Si did not result in changes of phenol oxidase activity in the hemolymph of larval D. saccharalis, the activity of this enzyme was greater in larvae fed with IAC91-1099 plants than in those fed with SP80-3280 plants.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…These results are in agreement with [66], who also found similar results when studying a soil dwelling herbivore interacting with sugarcane and Si. However, [25] observed increased values of phenol oxidase activity in the hemolymph of H. armigera larvae fed on the Si-fertilized model grass Brachypodium distachyon. Despite Si did not result in changes of phenol oxidase activity in the hemolymph of larval D. saccharalis, the activity of this enzyme was greater in larvae fed with IAC91-1099 plants than in those fed with SP80-3280 plants.…”
Section: Discussionmentioning
confidence: 81%
“…Another way to assess the negative effects of Si over herbivore insects would analyzing their immune system [25]. The insect immune system consists of structural barriers and active responses against foreign elements that enter the haemocoel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ganapathy et al [11] con rmed that highest per cent reduction of pod borer of green gram in potassium silicate @ 0.5% + gibberellic acid @ 50 ppm (54.87%) followed by potassium silicate @ 1% + gibberellic acid @ 100 ppm (51.79%) and silicic acid @ 0.2% + gibberellic acid @ 100 ppm (49.35%). Similarly, NuamboteYobila et al [12] revealed that Si treated plants disturbed the larval growth of FAW larvae only from the corn strain but not from the rice strain. Tarikul Islam et al [13] reported that the lower integument resistance of larvae when fed on Si supplemented plants could contribute to their vulnerability to natural enemies and high polyphenol oxidase activity in the haemolymph led to delayed development.…”
Section: Discussionmentioning
confidence: 91%
“…The impacts of plant antiherbivore defence on insect immunity have been much neglected (Islam et al, 2022). To our knowledge, there are no reports of the effects of Epichloë defences on herbivore immunity traits, and the effects of Si defences on herbivore immunity are poorly understood, with just two studies to date reporting that Si alone has no clear effects on chewing herbivore immunity (Frew et al, 2017; Islam et al, 2022). Frew et al (2017) reported that Si defences did not affect the immunity of a root‐feeding insect whereas Islam et al (2022) found that immunity of H. armigera was not affected by Si alone.…”
Section: Introductionmentioning
confidence: 99%